Critical Review of Post-COVID Cost Analysis in General Wards of Selected Private Hospitals in Nagpur City (International Journal of Food and Nutritional Sciences, 2023)
Globally, the COVID-19 pandemic has had a significant impact on healthcare systems, posing hitherto unheard-of difficulties for many hospitals in terms of patient care, resource allocation, and financial administration. It is crucial to assess the financial effects and implications for healthcare institutions as the world progresses past the acute phase of the epidemic. This critical study concentrates on the post-COVID cost analysis in the general wards of several private hospitals in Nagpur, India.This review's main goal is to investigate the financial effects of caring for COVID-19 patients in general wards, with a focus on contrasting the price structures of private healthcare facilities in Nagpur City. To do this, a thorough research of the literature is carried out in order to collect information and understanding regarding